Skim Wang Khairat Kematian (SWKK) di Malaysia Kajian Awal Menurut Adat Melayu dan Hukum Syarak - Setiyawan Gunardi; Azman Ab. Rahman; Ahmad Zaki Salleh; Syed Mohd Najib Syed Omar; Khairunneezam Mohd Noor; Zawin Hannan Sofea Shahbuddin (Usuli Faqih Research Centre PLT., 2024)
Vol. 30 No. 1